2020
DOI: 10.1002/ange.202003910
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly Engineered 6FDA‐Based Polyimide Membranes for Sour Natural Gas Separation

Abstract: Glassy polyimide membranes are attractive for industrial applications in sour natural gas purification. Unfortunately, the lack of fundamental understanding of relationships between polyimide chemical structures and their gas transport properties in the presence of H2S constrains the design and engineering of advanced membranes for such challenging applications. Herein, 6FDA‐based polyimide membranes with engineered structures were synthesized to tune their CO2/CH4 and H2S/CH4 separation performances and plast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…This behavior is similar to that of glassy polymers and originates from large differences in the diffusion rates for molecules of slightly different sizes and shapes. [45,46] In essence, for slightly larger molecules, the jump rate between bordering open spaces in a rigid glassy polymer decreases strongly. For polyphosphazene polymers, it has been demonstrated that the T g can be affected by introducing different substitution groups.…”
Section: Resultsmentioning
confidence: 99%
“…This behavior is similar to that of glassy polymers and originates from large differences in the diffusion rates for molecules of slightly different sizes and shapes. [45,46] In essence, for slightly larger molecules, the jump rate between bordering open spaces in a rigid glassy polymer decreases strongly. For polyphosphazene polymers, it has been demonstrated that the T g can be affected by introducing different substitution groups.…”
Section: Resultsmentioning
confidence: 99%
“…Polymeric materials designed for use in membrane-based natural gas purification application are numerous nowadays in the literature, though not all aspects have been entirely covered in this area. Several polymeric classes have been studied for membrane-based gas separation applications, such as polysulfone, , poly­( p -phenylene oxide), cellulose acetate, , polymers with intrinsic microporosity (PIM), polyimides, , polyazoles (polyoxadiazoles and polytriazoles), , and so on.…”
Section: Introductionmentioning
confidence: 99%
“…In order to minimize signal transmission crosstalk, interconnection resistance-capacitance delay in communication, the dielectric constant and dielectric loss of the dielectric need to be reduced as much as possible. 3 As a common engineering plastic, polyimide (PI) is widely used in gas separation, [4][5][6] electromagnetic shielding and absorbing, 7,8 and thermal conductivity materials [9][10][11] due to its excellent mechanical properties and corrosion resistance. However, since the dielectric constant of polyimides is around 3.2, which is not suitable for the current low dielectric constant requirement, plenty of methods are used to modify polyimides to make its dielectric constant meet the low dielectric constant requirement (k < 3.0).…”
Section: Introductionmentioning
confidence: 99%